The comparative effectiveness of demineralized bone matrix, beta-tricalcium phosphate, and bovine-derived anorganic bone matrix on inflammation and bone formation using a paired calvarial defect model in rats - Khoshzaban A; Mehrzad S; Tavakoli V; Heidari Keshel S; Reza Behrouzi G; Bashtar M (Dove Medical Press, 2011)
Ahad Khoshzaban1,2,3, Shahram Mehrzad1, Vida Tavakoli2, Saeed Heidari Keshel2, Gholam Reza Behrouzi2, Maryam Bashtar2 1Iranian Tissue Bank Research and Preparation Center, Imam Khomeini Hospital Complex, 2Stem Cells Preparation Unit, Eye Research Center, Farabi Hospital, Tehran University of Medical Science, 3Dental Bio Material Department, Tehran University of Medical Science, Faculty of Dentistry, Tehran, Iran Background: In this study, the effectiveness of Iranian Tissue Bank–produced demineralized bone matrix (ITB-DBM), beta-tricalcium phosphate (ßTCP), and Bio-Oss® (Geistlich Pharma AG, Wolhusen, Switzerland) were evaluated and compared with double controls. The main goal was to measure the amount of new bone formation in the center of defects created in rat calvaria. Another goal was to compare the controls and evaluate the effects of each treatment material on their adjacent untreated (control) defects. Methods: In this study, 40 male Wistar rats were selected and divided into four groups, In each group, there were ten rats with two defects in their calvarias; one of them is considered as control and the other one was treated with ITB-DBM (group 1), BIO-OSS (group2), and ßTCP (group 3), respectively. But in group 4, both defects were considered as control. The amount of inflammation and new bone formation were evaluated at 4 and 10 weeks. In the first group, one defect was filled with ITB-DBM; in the second group, one defect was filled with Bio-Oss; in the third group, one defect was filled with ßTCP; and in the fourth group, both defects were left unfilled. Zeiss microscope (Carl Zeiss AG, Oberkochen, Germany) and Image Tool® (version 3.0; University of Texas Health Science Center at San Antonio, San Antonio, TX) software were used for evaluation. SPSS Statistics (IBM Corp, Somers, NY) was used for statistical analysis. Results: Maximum bone formation at 4 and 10 weeks were observed in the ITB-DBM group (46.960% ± 4.366%, 94.970% ± 0.323%), which had significant difference compared with the other groups (P < 0.001). Ranking second was the Bio-Oss group and third, the ßTCP group. Bone formation in the group with two unfilled defects was much more significant than in the other controls beside the Bio-Oss and ßTCP after 10 weeks (29.1 ± 2.065, 29.05 ± 1.649), while this group had the least bone formation compared with the other controls at week 4 (2.100% ± 0.758%, 1.630% ± 0.668%, P < 0.001). Conclusion: Overall, the ITB-DBM group showed the best results, although the results for other experimental groups were unfavorable. The authors conclude that human DBM (ITB-DBM) should be offered as an alternative for bone regeneration in animals, such as horses, as well as in humans, especially for jaw reconstruction. In relation to bone regeneration in control defects, the effect of experimental material on controls was apparent during the initial weeks. Keywords: ßTCP, Bio-Oss, bone regeneration, DBM